Proceedings of the 70th Congress of the Italian Embryological Group-Italian Society of Development and Cell Biology (GEI-SIBSC) - The Scientific Committee (European Journal of Histochemistry, 2025)
Proceedings of the 70th Congress of the Italian Embryological Group-Italian Society of Development and Cell Biology (GEI-SIBSC) - Modena, 10-13 June 2025